TEACHING EVALUATION OF THE GERONTOGERIATRIC NURSING DISCIPLINE INTHE NURSING GRADUATION COURSE AT FURG - Bárbara Tarouco da Silva; Silvana Sidney Costa Santos (Universidade Federal do Paraná, 2007)
Brazilian aged population has been increasing fast, bringing about the need for health professionals' qualification,specially nurses. This study objectified the teaching evaluation of the Gerontogeriatric nursing discipline. Qualitative research, case-study type, performed by the Nursing Department of Fundação Universidade Federal do Rio Grande (FURG). During data collection,recorded interviews were used with a total of 26 students. Through the thematic analysis, the following categories emerged: I -Teaching Contents; II - Attitude change to aged people after the classes; III - Conditions acquired or not in elders' care after thediscipline; IV - Suggestions. The research revealed as an evaluation tool for the Gerontogeriatric nursing discipline, included asobligatory in the Pedagogical Political Project of the FURG ́s Nursing Department, considering that the nursing object is the humanbeing: child, adolescent, adult or aged.